Metode Discovery Learning Uuntuk Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Turunan Fungsi di Kelas XI SMA - Sari Nusantara Putri (Social Science Studies, 2022)
This research aims to improve the learning outcomes of grade XI students on Function Derivative materials using the Discovery Learning method. This research is a classroom action study with the research subjects of class XI students. The data collection techniques used in this study are observations, questionnaires, and tests. The data obtained is analyzed qualitatively and quantitatively. Based on the results of observations made in cycles I and II seemed to have no effect, then based on the results of positive student response questionnaires then based on test results also increased, namely in cycle I classically by 62% with an average of 65, 91 and cycle II classically 88% with an average score of 72,45